Equivalences of some forms of the change of variable formula and the fundamental theorem of calculus - Tandra, Haryono (Teaching Mathematics and Computer Science, 2014)
We discuss an interplay between some versions of the Change of Variable Theorem and the Fundamental Theorem of Calculus for the Riemann integral. We show that the two theorems are equivalent, and that for both theorems to be true it suffices to assume two particular formulas derived from them. In the realm of teaching, this material might be among our interests.